2018
DOI: 10.1186/s12885-018-4185-0
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of acute oxaliplatin-induced neuropathy and its impact on treatment in the first cycle: a systematic review

Abstract: BackgroundAlthough acute oxaliplatin-induced neuropathy (OXIPN) is frequently regarded to be transient, recent studies have reported prolongation of infusion times, dose reduction and treatment cessation following the first dose of oxaliplatin in quarter of patients. Acute OXIPN is also a well-established risk factor for chronic neuropathy. However, there is underreporting of these parameters during the acute phase (≤ 14 days). This paper systematically reviews the incidence of acute OXIPN and its impact on tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 48 publications
2
65
1
4
Order By: Relevance
“…In contrast to the previous reports [4,16], haematological toxicity was the main adverse advent recorded for dose reduction, followed by neuropathy plus haematological toxicity and neuropathy alone, respectively, across cycles ( Figure 5). Neuropathy along with any other adverse events resulted in dose reduction in 37-51% of the patients in any given cycle.…”
Section: Impact Of Oxaliplatin-induced Neuropathic Pain and Other Checontrasting
confidence: 98%
See 2 more Smart Citations
“…In contrast to the previous reports [4,16], haematological toxicity was the main adverse advent recorded for dose reduction, followed by neuropathy plus haematological toxicity and neuropathy alone, respectively, across cycles ( Figure 5). Neuropathy along with any other adverse events resulted in dose reduction in 37-51% of the patients in any given cycle.…”
Section: Impact Of Oxaliplatin-induced Neuropathic Pain and Other Checontrasting
confidence: 98%
“…Additionally, patients who received FOLFOX treatment had longer survival times, followed by XELOX and oxaliplatin monotherapy (11.5 vs 9 vs 4.5 months, respectively). Survival analysis (by factor) confirmed that patients who completed 8 cycles of chemotherapy and those who received >850 mg/m 2 cumulative dose of oxaliplatin had longer survival times, indicating that delay or cessation leads to poorer treatment outcome as reported in this and prior studies [12,16]. Moreover, the IDEA clinical trial study failed to confirm overall noninferiority of 3 vs. 6 months treatment of XELOX and FOLFOX regimens but did show inferiority of shorter duration FOLFOX treatment in high risk subgroups [25][26][27].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Neuropathy is a common side effect of chemotherapy regimens typically used for colorectal cancer that contain oxaliplatin . Periodic or chronic diarrhea occurs in approximately one‐half of colorectal cancer survivors .…”
Section: Selected Cancersmentioning
confidence: 99%
“…The large majority (89%) of a cohort of 346 patients under fluorouracil, leucovorin, and oxaliplatin (FOLFOX) reported at least one symptom of acute oxaliplatin neurotoxicity within the first cycle, namely sensitivity to cold (71%), throat discomfort (63%), or muscle cramps (42%), with a peak at day 3, later improvement, and incomplete remission between treatments . According to a systematic review, acute oxaliplatin neuropathy (Common Terminology Criteria Adverse Events, CTCAE grades 1‐4) occurred in 4% to 98% of patients, with moderate to severe toxicities commonly encountered in patients receiving a large dose of oxaliplatin (> 85 mg/m 2 ) and/ or combined drugs …”
Section: Clinical Aspects Of Pipnmentioning
confidence: 99%